A Low-Cost Label-Free AFB(1) Impedimetric Immunosensor Based on Functionalized CD-Trodes - Foguel, Marcos Vinicius [UNESP]; Giordano, Gabriela Furlan [UNESP]; Sylos, Celia Maria de [UNESP]; Carlos, Iracilda Zeppone [UNESP]; Pupim Ferreira, Antonio Aparecido [UNESP]; Benedetti, Assis Vicente [UNESP]; Yamanaka, Hideko [UNESP] (Mdpi Ag, 2016)
This work describes the investigation of a label-free immunosensor for the detection of aflatoxin B-1 (AFB(1)). CD-trodes (electrodes obtained from recordable compact disks) were used as low-cost and disposable transducers after modification with a self-assembled monolayer (SAM) of lipoic acid. The anti-aflatoxin B1 antibody was immobilized via EDC/NHS activation, followed by blocking with bovine serum albumin and immunoassays with AFB(1). The optimization of analytical parameters and the detection were carried out using electrochemical impedance measurements. Using chemometric tools, the best conditions for the immunosensor development were defined as: anti-AFB(1) antibody at 1:2000 dilution and surface blocking with 0.5% bovine serum albumin, both incubated for 1 h, and antibody-antigen immunoreaction for 30 min. The impedimetric immunosensor showed a linear range from 5 x 10(-9) to 1 x 10(-7) mol . L-1 (1.56-31.2 ng . mL(-1)), limit of detection and limit of quantification, respectively, 3.6 x 10(-10) and 1.1 x 10(-9) mol . L-1 (0.11 and 0.34 ng.mL(-1)). The proposed immunosensor was applied to analyze peanut samples.
Keywords: aflatoxin B-1; immunosensor; electrochemical impedance spectroscopy